2006
DOI: 10.1074/jbc.m606317200
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β4 Regulates Migratory Behavior of Keratinocytes by Determining Laminin-332 Organization

Abstract: Whether ␣6␤4 integrin regulates migration remains controversial. ␤4 integrin-deficient (JEB) keratinocytes display aberrant migration in that they move in circles, a behavior that mirrors the circular arrays of laminin (LM)-332 in their matrix. In contrast, wild-type keratinocytes and JEB keratinocytes, induced to express ␤4 integrin, assemble laminin-332 in linear tracks over which they migrate. Moreover, laminin-332-dependent migration of JEB keratinocytes along linear tracks is restored when cells are plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
191
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(206 citation statements)
references
References 67 publications
(73 reference statements)
11
191
3
1
Order By: Relevance
“…Sehgal et al showed that β4 integrin-deficient (JEB) keratinocytes display aberrant migration; they move in circles, a behavior that mirrors the circular arrays of laminin-332 in their matrix [95]. In contrast, wild-type keratinocytes, and JEB keratinocytes induced to express β4 integrin, assemble laminin-332 in linear tracks over which they migrate.…”
Section: Section 2 Part 3: Laminin-332 Signal Transduction In Cancermentioning
confidence: 99%
“…Sehgal et al showed that β4 integrin-deficient (JEB) keratinocytes display aberrant migration; they move in circles, a behavior that mirrors the circular arrays of laminin-332 in their matrix [95]. In contrast, wild-type keratinocytes, and JEB keratinocytes induced to express β4 integrin, assemble laminin-332 in linear tracks over which they migrate.…”
Section: Section 2 Part 3: Laminin-332 Signal Transduction In Cancermentioning
confidence: 99%
“…Although a 6 b 4 can regulate the motility of cultured keratinocytes, 72,73 it remains uncertain whether this integrin has important pro-migratory roles in wound re-epithelialization. It is clear that a 6 b 4 is not sufficient for normal wound reepithelialization in the absence of b 1 integrins, since b 1 -null epidermis shows severe migration defects.…”
Section: Autonomous Keratinocyte Functionsmentioning
confidence: 99%
“…73 a 3 b 1 . In vivo and in vitro studies have identified several roles for integrin a 3 b 1 in regulating keratinocyte functions that may contribute to wound healing, including ECM deposition and organization, 74,75 cell polarization and migration, 34,53 cell survival, 62 cell proliferation, 76 and secretion of ECM proteases and pro-angiogenic factors.…”
mentioning
confidence: 99%
“…Recent studies have suggested that the migration and invasion of tumor cells is controlled, in part, dependent on a6b4 integrin/ Rac1 signaling. 51,52 This pathway signals focus to the major regulator of cellular actin dynamics, cofilin, 53 its activity dependent on phosphorylation/dephosphorylation at Ser3, modulating cytoskeletal organization and cell migration. 14-3-3zeta protein involves in the regulation of cellular actin structures through the maintenance of phosphorylated-cofilin levels.…”
Section: Cell Skeleton Invasion and Metastasismentioning
confidence: 99%